ANALISIS FAKTOR KEDISIPINAN MAHASISWI (Studi Kasus di IDIA Prenduan Sumenep Tahun 2022) - Afifah, Afifah; Fitrianingsih, Fitrianingsih (STAI Denpasar Bali, 2023)
Discipline in an educational institution is an element that is needed as well as the most effective means in the learning process. Discipline provides many benefits for maintaining a balance between the child's inclination and desire to do something with the rules needed in the environment. And efforts that can be made in instilling a disciplined attitude towards children are providing good examples and habituation to actions that are carried out every day. This research focused on student discipline and the supporting and inhibiting factors of female student discipline at IDIA Prenduan Sumenep. This study uses descriptive qualitative research with a case study type of research. Sources of data in this study were obtained from leaders, naibah, ustadzah and female students. by using interview and observation methods. From this method the researcher analyzed the data and information obtained from the informants, by reducing the data, presenting the data and finally concluding so as to produce information that is in accordance with the focus of the research. Discipline that is applied in the IDIA environment is divided into 3 parts, namely the sharia field (worship) such as congregational prayers, tahajjud prayers, tadarus muajjah and other worship activities. In the field of language, such as female students, they must use the official language (English and Arabic) as everyday language, and in the field of qonun (regulations on clothes that may be used both inside and outside the dormitory, and time for studying. Factors supporting a growing awareness in female students, character or personality that is formed in female students, motivation that can raise the spirit of female students, and tazwidul mufrodat agenda, inhibiting factors that are inherited from home or bad behavior, lack of knowledge of nahwu and sorof, and wrong and socializing or wrong in choosing Friend.